(untitled) (World Economics and Finance Bulletin, 2022)
Financial fragility is one of the most important problems facing the Iraqi economy. Financial fragility is represented by the weak efficiency of the financial system in mobilizing the financial resources needed to finance the public budget, as well as financing financial investments that support economic activity. This is all due to the miscalculation of public revenues, public expenditures, the misallocation of financial resources, and the nature of the public budget structure in Iraq, which weakened the ability of the financial authority in Iraq to manage financial resources, as well as the inability of that financial authority to provide the financial space needed to finance the public budget deficit and face Internal and external shocks when they occur.